-1x-6x=9-8x

Simple and best practice solution for -1x-6x=9-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1x-6x=9-8x equation:


Simplifying
-1x + -6x = 9 + -8x

Combine like terms: -1x + -6x = -7x
-7x = 9 + -8x

Solving
-7x = 9 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-7x + 8x = 9 + -8x + 8x

Combine like terms: -7x + 8x = 1x
1x = 9 + -8x + 8x

Combine like terms: -8x + 8x = 0
1x = 9 + 0
1x = 9

Divide each side by '1'.
x = 9

Simplifying
x = 9

See similar equations:

| 10x+8y*2x= | | 6+5x+4=15 | | 4y+1=22 | | 9x+10=-53 | | (2b+4)(b-3)=600 | | 3+3n-2n=4 | | 672x=175 | | 0=3n-3n | | 5(3)+3(3)-3+5= | | -6n+6n=4 | | 7-2(x+3)-x=x+5 | | n+n+(n-3+4)+4n=4n | | 6x^2+15x-25=0 | | f-f+9f-(f-3)=f+f | | 4m-12m+(m-3)=2m | | 3x+14+2x-4=90 | | -2-5(r-2)=-3(1-2r) | | 156-5x=31x+20 | | .833333x-.2x+4=.7x | | 506-?=265 | | 7(2n-4)-5=-40+7n | | 4ln(x-4)=4 | | (p+3)x^2+(2p+3)x+p+5=0 | | -.4x-9=.9 | | 5x+14=-28x-9x | | 19-3e=2-5(e+1) | | (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) |

Equations solver categories